1997
DOI: 10.1093/occmed/47.6.357
|View full text |Cite
|
Sign up to set email alerts
|

Contamination incidents among doctors and midwives: reasons for non-reporting and knowledge of risks

Abstract: A 6-month retrospective self-administered questionnaire study of 482 doctors and 380 midwives in two NHS Trusts was undertaken. The response rate was 384 (80%) and 293 (77%) respectively. The study revealed that only nine per cent of doctors and 46% of midwives had reported the contamination incidents they had received. The doctors' main reason for non-reporting was 'too time consuming' and midwives' was 'did not consider anything could be done', although their awareness of the active management of contaminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 10 publications
3
32
0
Order By: Relevance
“…From anecdotal evidence it seems that many nurses and medical doctors would rather not know their status following injury for fear of the potentially devastating impact a positive result could have on career. The other reasons for not reporting may be fear of disciplinary action due to negligence of the health care workers or the inability to influence the outcome following injury [35,36]. Health care workers may thus perceive reporting a needle stick injury as futile.…”
Section: Discussionmentioning
confidence: 99%
“…From anecdotal evidence it seems that many nurses and medical doctors would rather not know their status following injury for fear of the potentially devastating impact a positive result could have on career. The other reasons for not reporting may be fear of disciplinary action due to negligence of the health care workers or the inability to influence the outcome following injury [35,36]. Health care workers may thus perceive reporting a needle stick injury as futile.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, employees may consider follow up too time consuming. 10 Risk assessment and management Overall, OH staff were more consistent in assessing and managing exposures. This is not surprising; the concept of risk assessment is fundamental to OH practice, but may be alien to junior medical staff in A&E. OH staff also have more experience in managing body fluid exposures, and have more time to contact the source patient's medical team for information or to organise source patient testing.…”
Section: Main Findingsmentioning
confidence: 99%
“…Additionally, surveillance systems are vulnerable to under-reporting and missing data, particularly if based on voluntary reports. Under-reporting of occupational injuries is well described in the literature,22 30 31 and may have introduced bias. However, high-risk injuries are less likely to be under-reported,31 32 making it less relevant to this study, which focuses on PEP-uptake behaviour in a high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Risk perception may not always be appropriate. For example, De Carli and colleagues demonstrated that HCWs failed to correctly identify the HIV status of a majority of emergency patients,42 and a number of studies have found that HCWs underestimated risks from occupational exposures to needles 21 30 43. Yet, HCWs have been shown to modify their risk behaviour according to their own perceptions of HIV transmission risk in other, but comparable situations 44.…”
Section: Discussionmentioning
confidence: 99%